Motivation of users of a Family Health Strategy in health groups - Silva de Freitas, Caroline (2015)
Objective: To identify reasons for adhesion and permanence in health promotion groups among participants. Methods: The study included 27 users of the Estratégia de Saúde da Família - ESF (Family Health Strategy) in the municipality of Santa Maria, Rio Grande do Sul, from August to November 2014. An adapted questionnaire about motivation for group activities was used, with the main adhesion and permanence variables distributed in order of priority. Data were tabulated in MS Excel 2003 and analyzed using simple descriptive statistics. Results: The results showed that the factors that motivate users to join health promotion groups in Primary Care are related to health improvement (n=19, 70%), physical performance improvement (n= 15, 56%), self-esteem improvement (n=14, 52%), and others. The reasons related to the permanence in the groups are related to health maintenance (n=18, 67%), attention and encouragement received from the teacher (n=18, 67%), attention received from the staff (n=15, 56%) and stress reduction (n=15, 56%). Conclusion: According to the data on the reasons for adhesion and permanence in the groups, individuals tend to seek better health and quality of life. In addition, encouragement for a healthier lifestyle and also the support from professionals and other people involved in the activities imply greater permanence of users in the group.